Synthesis of Highly Functionalized Quinazoline-2,4(1H,3H)-diones from Isocyanides, Aniline and Isocyanate via Cu-Catalyzed Intermolecular C-H Activation Reactions - Nematpour, Manijeh; Dastjerdi, Hossein Fasihi; Jahani, Mehdi; Tabatabai, Sayyed A. (Letters in Organic Chemistry, 2020)
A simple and appropriate procedure for the synthesis of quinazoline-2,4(1H,3H)-dione derivatives from isocyanides, aniline and isocyanate via the Cu-catalyzed intramolecular C-H activation reaction is reported. The advantages of this method are one-pot conditions, accessible starting materials- catalyst, high yield of products, and short reaction times. The structures are confirmed spectroscopically (1H- and 13C-NMR, IR and EI-MS) and by elemental analyses.
Keywords: Cu-catalyzed